"Real, but Glossy": technology and the practical pursuit of magic in modern weddings - Massimi, Michael; Harper, Richard; Sellen, Abigail (CSCW '14: Proceedings of the 17th ACM conference on Computer supported cooperative work & social computing, 2014)
Planning a wedding is arguably one of the most complicated collaborative tasks people ever undertake. Despite the commonplace use of technologies in "wedding work," little research has looked at this from an HCI perspective. Based on an interview study, we illustrate how technology is used to deliver the sought-after fantasy and a practical, yet entertaining, affair. We identify four ways that technology helps people do this: (a) by allowing much of the practical planning work to become "invisible;" (b) by easing navigation through the delicate rules of family configurations made manifest in the guest list; (c) by helping create a spectacle-like event that adroitly balances excess and realism; and (d) by documenting the wedding in ways that allows re-experiencing the magic after the event. The paper concludes by discussing the implications of this pursuit on social graphs, place, and photography, contributing to the literature on technology and major life events.